The Interrelation of Language Learning Strategies and English Proficiency among Medical Students - Finaty Ahsanah; Dias Tiara Putri Utomo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study investigated language learning strategies used by medical students and its relation to students’ English proficiency. The study was conducted at Universitas Muhammadiyah Lamongan, the participant involved in this study were 74 medical students from three different departments; physiotherapy, midwifery, and pharmacy.  The language learning strategies data were obtained from the Oxford’s Strategy Inventory for Language Learning (SILL), while the English proficiency level was obtained from the students’ EPT scores. Data analysis was carried out using SPSS – descriptive statistics and Pearson Correlation. The findings revealed that the participants frequently used strategies were memory strategies by the mean of 3.11, followed by metacognitive strategies at 3.06, cognitive strategies at 2.97, social strategies at 2.95, compensation strategies at 2.94, and affective strategies at 2.91.  Meanwhile, the Pearson Correlation or ŕ value was .054 ≤ 0.05, and the sig. (2 tailed) value was .064 ≥ 0.05. It can be concluded that there was no interrelation between the use of language learning strategies and students’ English proficiency. Therefore, students’ English proficiency does not affect language learning strategies preference. The findings of this current study might be useful as input for English teachers and learners to build an effective classroom environment.